Research progress on stability control of surrounding rock in weakly cemented strata engineering in western China mining area - JI Hongguang; SUN Lihui; SONG Zhaoyang; ZHANG Yuezheng; WANG Jiuhong; MENG Zhiqiang (Meitan kexue jishu, 2023)
The mining strata in the western mining area of China are mainly composed of Jurassic and Cretaceous strata. The strata are characterized by low strength, poor cementation and easy disintegration, which belong to weakly cemented rocks. The surrounding rock of the weakly cemented stratum project is quite different from the stratum rock of the central and eastern mining areas. It is difficult to effectively guarantee the safety of the project by using traditional control technologies such as roof control of the working face and surrounding rock control of the roadway. Disasters such as large deformation and instability of the roadway, crushing of the working face, water inrush, sand inrush, rock burst and so on. Through a large number of investigations and laboratory experiments, the mechanical indexes such as tensile and compressive strength of weakly cemented rocks are much smaller than those of similar rocks in the central and eastern mining areas. The evaluation index system of the variation degree of weakly cemented rocks under the coupling of multiple factors is established, and the variation degree of weakly cemented rocks in typical mining areas is preliminarily obtained. Taking the weakly cemented rock in Hongqinghe Coal Mine as an example, it is found that the weakly cemented rock has the phenomenon of ‘phase transition’ under the action of force, water and other loads. The influence of cementation degree on the phase transition phenomenon is analyzed, and the ‘phase transition’ state characteristics and sensitivity parameters of weakly cemented coarse-grained sandstone are given. The dynamic development law of overburden caving zone and fracture zone and the large deformation law of roadway surrounding rock are studied and analyzed, which lead to the support crushing, water inrush and sand inrush disasters in the working face. The dynamic change expression of caving zone in different mining stages of large mining height working face in weakly cemented strata is deduced, and the support-surrounding rock interaction model is established. The working resistance of support during weighting and non-weighting of working face is given. Aiming at the loose and weak characteristics of weakly cemented strata, the double shell reinforcement technology of roadway surrounding rock is proposed, which can provide guarantee for safe mining of working face and control of roadway surrounding rock.